Deficit Irrigation and an IoT-Based System for Improving Yield and Water Use Efficiency of Winter Wheat Grown Under Semi-Arid Conditions - Salah Belkher; Basma Latrech; Wifak Bekri; Felix Markwordt; Mohamed Abdur Rahim; Corentin Dupont; Mohamed Ali Ben Abdallah; Hedi Daghari; Mourad Rezig (Agronomy)
In the context of water restriction, the adoption of innovative technology and water saving strategies is crucial to sustainable agriculture production. Thus, we sought to emphasize the contribution of precision irrigation based on Internet of Things (IoT) technology and smart sensors for optimizing irrigation water use. The effects of different drip irrigation regimes on total dry matter (TDM), grain yield (GY) and water use efficiency (WUE) of winter wheat grown on clay-loam soil under semi-arid conditions of Tunisia have been assessed for three consecutive growing seasons. The trial included fully irrigated (FI) treatment (100% of crop evapotranspiration (ETc)), two deficit irrigation treatments (DI1, DI2 corresponding to 75 and 60% of ETc, respectively) and rainfed treatment DI3, replicated three each. The results showed that TDM and GY increase with increasing irrigation amount. At harvest, the highest TDM and GY values were recorded under FI and DI1. Reducing irrigation amount by 40% (DI2) resulted in a significant grain yield reduction, quantified as 52.7, 45.7, 30.4%, respectively, for the three cropping seasons. Across all growing seasons and treatments, WUETDM values ranged between 4.11 and 6.32 Kg m−3. The highest values were achieved under rainfed treatment. However, no significant difference was observed between irrigated treatments, in particular, during 2022–2023 and 2023–2024. In terms of WUEGY, no significant difference was observed between the FI and DI1 treatments, while significant reductions were registered under DI2 and DI3. The adoption of deficit irrigation at 75% ETc based on smart tensiometers can be used as an effective strategy to optimize water use in winter wheat without compromising yield.